Optimising website services through the utilisation of intelligent software agents: theoretical foundations and practical implications. (1st January 2012) - Farzaneh, Mandana; Vanani, Iman Raeesi; Sohrabi, Babak
The joint application of web services and intelligent software agents leads to the creation of intelligent web services. Applying intelligent software agents (ISAs) would increase the capability of website administrators in responding to the user's needs at the right time and with high quality and safety. This paper intends to develop a conceptual framework through a comprehensive investigation of the broad literature of ISAs so as to assist the developers in designing and optimising the web services. The main goal of this paper is to represent a comprehensive framework based on the collection and classification of important services of websites as well as categorising the ISAs in order to be utilised in implementing these important services in order to improve the quality of service usage. This classification is based on a deep and complete review of the most applicable services in websites through the study of the top one hundred websites' services of the world through the most visited websites. Describing the classification of agents and their significant features has led to the identification of the main intelligent agents for implementing the services of websites in order to optimise the usage of such services.